The Influence of Defense Equipment Exports, Defense Equipment Imports, and the Defense Budget, on Economic Growth in Indonesia in 2017-2021 - Yollanda Lakshinta Harningrum; Suwito Suwito; Edy Sulistyadi (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The development of the defense industry is influenced by several factors such as the defense budget and military technology related to the export of defense equipment and the import of defense equipment. This study aims to examine how the influence of the defense budget, export of defense equipment, and import of defense equipment on economic growth. This research uses quantitative methods. The data used is secondary data in the form of a time series (2017-2021) obtained from SIPRI and Global Fire Power. The data processing technique uses Eviews 12. The data analysis technique used in this study is the classical assumption test, multiple linear regression, partial significance test (t test), simultaneous significance test (F test), and the coefficient of determination (R2). The results of this study indicate that 1) Exports of defense equipment have no effect on economic growth with a probability of 0.1154. 2) Imports of defense equipment have no effect on economic growth with a probability of 0.3494. 3) The defense budget has no effect on economic growth with a probability of 0.1225. 4) The independent variables simultaneously have no influence on the dependent variable. The conclusion from this study is that defense equipment exports, imports, and the defense budget have no effect on economic growth either partially or simultaneously in the 2017-2021 period.